Cerebral Arterial Territories Most Obstructed in Ischemic Stroke: Experience of a Tropical Low Income Practice Center - Assogba, Komi; Balogou, Koffi A.A.; Amegnidou, Mawulom K.; Belo, Mofou; Apetsè, Kossivi M.; Amadou, Abdoulatif (Journal of Neurology and Epidemiology, 2014)
Background: The cerebral arterial territory corresponds to a specific brain area irrigated by an artery. Stroke remains the leading cause of physical disability acquired wide world. We aimed to identify different arterial territories affected among patients hospitalized for ischaemic stroke. Materials and Methods: We have conducted a retrospective study in the neurology department of our tertiary hospital. The study has carried out inpatients presenting with clinical features of ischaemic stroke from January to December 2012. Their brains CT scan have shown infarction areas. Patients excluded were those presented with clinical manifestations of stroke but did not perform a CT scan and those with a hemorrhagic stroke or transient ischaemic attack with normal CT scan. Results: We have analyzed 64 cases among 408 inpatients which have given a frequency of 15.7%. The sample has included 31 (48.4%) men for 33 (51.6%) women. The mean age was 61.7 years. The clinical features were marked by motor deficit (right or left) in 98.4% followed by aphasia 35.9% and impaired consciousness, 26.6%. We have observed 31(48.4%) infarction in the right hemisphere and 36(56.3%) in the left. Two patients (3.1%) had bilateral brain infarcts. Depending on the arterial territories obstructed, the middle cerebral artery was the most affected with 76.6% followed by the anterior cerebral artery, 14.1%, the anterior choroid artery, 7.8% and the cerebellar arteries with 3.1%. The cortical and central arteries branches were affected in 82.7% and 68.8% respectively. Conclusion: This study has highlighted the useful tools to recognize arteries areas frequently affected in ischaemic stroke. The affected brain area can easily be attached to an arterial territory with a specific anatomic and radioclinic correlation syndrome.